Potentials of python programming for the development of creative thinking in mathematics - Binotto, Rosane Rossato (2023)
This article presents the results of a study aimed at identifying and analyzing indications of mathematical creativity in programming activities developed in Python, throughout a professional development course involving undergraduate students majoring in Mathematics, High school students, and teachers from K-12 Education. The participants responded to an open-ended question and implemented their solutions in Python, with the code analyzed in this article. The research followed a qualitative approach, utilizing Content Analysis to categorize the obtained data. Through the analysis, we found that Python programming for open-ended problem-solving holds potentials for fostering creative thinking in mathematics, facilitating simulation, debugging, reflection on the process, motivation, and engagement, leading to creative solutions.